A Review of Past Research and Some Future Perspectives Regarding Titanium Alloys in Biomedical Applications - Alex-Barna Kacsó; Ildiko Peter (Journal of Functional Biomaterials)
This review paper provides a comprehensive synthesis of the current advancements in investigations of different titanium-based alloys, including pure titanium, commercially available Ti6Al4V, and modified alloys, such as Ti-Nb-Zr-Fe alloys, for biomedical applications. Several researchers have explored the effects of alloying elements and processing techniques on enhancing the mechanical, chemical, and biological properties of these materials. Ti-Nb-Zr-Fe alloys are of particular interest due to their potential to address critical requirements in medical applications, including reduced Young’s modulus, superior corrosion resistance, biocompatibility, and mechanical strength. Despite substantial progress, the detailed mechanisms for optimizing these properties remain underexplored in the current literature. The main objective of the present review paper is to emphasize the importance of ongoing investigations aimed at overcoming challenges such as biocompatibility concerns, fatigue resistance, and wear under biological conditions. By critically analyzing existing data, this study highlights gaps in knowledge and identifies opportunities for advancing research on these alloys. Specifically, this review paper highlights the need for targeted studies to reduce the Young’s modulus and improve other critical characteristics of Ti-Nb-Zr-Fe alloys to better meet the demands of orthopedic implants, dental prosthetics, and cardiovascular devices. Even if the current scientific literature is ample on this topic, we consider that through this review we can positively contribute to the collective effort in this field trying to fill some gaps, including some updates on the topic, time frames, advantages, and limitations, and pave the way for further advancements that could revolutionize biomedical implant technology. The review encompasses studies performed over the last 5 decades, specifically from 1975 to 2025, to ensure the inclusion of the most relevant and up-to-date research. This approach aims to highlight the significant progress made while situating the findings within the broader context of ongoing investigations.